2008
DOI: 10.1074/jbc.m803255200
|View full text |Cite
|
Sign up to set email alerts
|

ADP Competes with FAD Binding in Putrescine Oxidase

Abstract: Putrescine oxidase (PuO, 4 EC 1.4.3.10) is a flavin-containing amine oxidase involved in polyamine degradation. It catalyzes the oxidative deamination of putrescine (1,4-diaminobutane) into 4-aminobutanal with concomitant reduction of oxygen to hydrogen peroxide (Scheme 1). In addition, the oxidase also accepts other polyamines, like spermine and spermidine, which are involved in cell growth and differentiation and interact with nucleic acids (1, 2).PuO was first reported in the 1960s when it was isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…Recently, it was shown that ADP competes with FAD in putrescine oxidase, and the enzyme was isolated with ADP bound at the ADP binding site of FAD. 47 If ADP is added at a sufficiently high concentration to the reconstituted apoprotein−FAD complex, the rate of ADP incorporation should be limited by the FAD dissociation rate. We used this approach to determine the FAD ox dissociation rate constants.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was shown that ADP competes with FAD in putrescine oxidase, and the enzyme was isolated with ADP bound at the ADP binding site of FAD. 47 If ADP is added at a sufficiently high concentration to the reconstituted apoprotein−FAD complex, the rate of ADP incorporation should be limited by the FAD dissociation rate. We used this approach to determine the FAD ox dissociation rate constants.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…44−46 The apoprotein displaces the equilibrium toward the unstacked form of FAD by anchoring the 5′-ADP moiety throughout interaction with several amino acids of the consensus sequence located in the positively charged groove of the FAD binding site. The use of the ADP moiety as the major anchoring point to the apoprotein has been observed in several flavoenzymes, 47,54,55 and this phenomenon could be a general feature among the FAD binding proteins. Anchoring the ADP likely restricts the conformational sampling of the cofactor and may help the isoalloxazine to translocate into the active site.…”
Section: ■ Conclusionmentioning
confidence: 97%
“…To probe whether PuO could be converted to a covalent flavoprotein, an alanine residue corresponding to the linking cysteine in human MAO B was replaced by a cysteine. Intriguingly, the A394C PuO mutant was indeed able to form a covalent FAD–protein bond [73]. The ability to convert a noncovalent flavoprotein PuO into a covalent flavoprotein by a single amino acid replacement also confirms the self‐catalytic nature of covalent flavinylation.…”
Section: Roles Of Covalent Flavinylationmentioning
confidence: 94%
“…Results from a recent study on a sequence‐related amine oxidase have hinted at another rationale for covalent flavinylation. The bacterial putrescine oxidase (PuO) was shown to contain equal amounts of tightly but noncovalently bound FAD and ADP [73]. On the basis of the high degree of sequence identity between mammalian MAO and PuO, only one dinucleotide cofactor is expected to bind to PuO.…”
Section: Roles Of Covalent Flavinylationmentioning
confidence: 99%
“…19,21 The previous low FAD loading is related to competing binding of the inhibitor adenosine diphosphate to the active site. 22 The nearly total FAD occupancy of purified PuO derivatives can be explained by optimized PuO production conditions at low temperature (18°C) in TB complex media. The UV/Vis spectra showed typical characteristics of flavoenzymes ( Fig.…”
mentioning
confidence: 99%